PELATIHAN PEMBUATAN MINUMAN KOPI COLD BREW DI KAMPUNG TAMAN BACA KELUARGA , CIMONE - Jimmy Muller Hasoloan Situmorang; Vasco Adato H. Goeltom; Kevin Gustian Yulius (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Community Service (PKM) is one of the implementations of the Tri Dharma of Higher Education, aimed at providing tangible benefits to society. This PKM activity was conducted by a group of instructors from the Faculty of Tourism, Universitas Pelita Harapan, at Kampung Taman Baca Keluarga, Cimone. The theme of the program was Cold Brew Coffee Making Training, designed to improve the community’s skills in preparing coffee-based beverages. Cold brew is a coffee brewing method that involves steeping ground coffee in cold water for a specific period, resulting in a smooth flavor with low acidity. Through this training, participants were expected to gain new knowledge about the cold brew process, understand proper basic techniques, and develop creativity in presentation. In addition to providing insights into coffee beverage innovation, this activity was also intended to open business opportunities for the local community. The implementation results of PKM showed high enthusiasm among participants, as reflected in their active involvement during practice and discussion. Participants found the materials relevant, easy to apply, and beneficial for improving daily skills. Thus, this activity positively contributes to community empowerment by enhancing competencies in modern beverage preparation.